Simulation and Experiment of Spiral Soil Separation Mechanism of Compound Planter Based on Discrete Element Method (DEM) - Lianjie Han; Wei Yuan; Jinjin Yu; Jiajun Jin; Dongshen Xie; Xiaobo Xi; Yifu Zhang; Ruihong Zhang (Agriculture, 2022)
In order to solve the problems of blocking the drainage ditch and reducing the soil flatness caused by soil accumulation when using compound planter with plowshare to ditch, a spiral soil separation mechanism (SSSM) is designed. The SSSM is analyzed. In order to obtain the optimal parameters of the SSSM, based on the discrete element method, the multifactor test is carried out with the embedded depth, pitch, and rotation speed of the spiral blade as the test factors and the soil separation distance and uniformity as the evaluation index. The optimal parameters are the embedded depth 49 mm, pitch 331 mm, and rotation speed of the spiral blade 318 r min−1. The field experiment is carried out with these parameters, with soil separation distance 900 mm and standard deviation of soil height 7.8 mm, which is consistent with the simulation results. No blockage of drainage ditch was found, which shows that this device can effectively solve the problem. This study can provide a reference for the design of soil separation equipment using spiral soil separation device.